Instruction for commencement of brick works at toilet zone area of all floors of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding instruction for commencement of brick works at toilet zone area of all floors of BRAC University new campus project.